درجة ممارسة مديرى المدارس لاتخاذ القرارات وعلاقته بالأداء الوظيفى من وجهة نظر المرشدين التربويين فى المدارس الثانوية بمحافظة الزرقاء - الشخوت، فريال عويد وقعان (الجمعية المصرية لأصول التربية, 2018)
هدفت الدراسة التعرف على درجة ممارسة مديري المدارس لاتخاذ القرارات وعلاقته بالأداء الوظيفي من وجهة نظر المرشدين التربويين في المدارس الثانوية بمحافظة الزرقاء. تكونت عينة الدراسة من (240) مرشدا ومرشدة من العاملين في المدارس الثانوية في مديريات التربية والتعليم في محافظة الزرقاء. وطبقت الدراسة في الفصل الدراسي الأول 2017 / 2018، واستخدمت الدراسة المنهج الوصفي المسحي. وبعد تحليل البيانات توصلت الدراسة إلى النتائج الدراسة: أن درجة اتخاذ القرارات لدى مدراء المدارس الثانوية في الزرقاء جاءت بمستوى مرتفع. عدم وجود فروق ذات دلالة إحصائية في مستوى اتخاذ القرار والأبعاد المكونة له لدى مدراء المدارس الثانوية في الزرقاء تعزى لمتغيرات الجنس، والمؤهل العلمي، وسنوات الخبرة، ونوع المدرسة. أن مستوى أداء الوظيفي للمرشدين التربويين في المدارس الثانوية بمحافظة الزرقاء مرتفعة، وجود فروق ذات دلالة إحصائية في مستوى الأداء الوظيفي للمرشدين التربويين في محافظة الزرقاء تبعا لمتغير الجنس، ولصالح المرشدات. ولصالح مرشدي المدارس الخاصة، ولصالح المرشدين التربويين حملة مؤهل البكالوريوس، وجود علاقة ارتباطية موجبة ودالة إحصائيا بين درجة اتخاذ القرارات لدى مديري المدارس الثانوية ومستوي الأداء الوظيفي لدى المرشدين التربويين في المدارس الثانوية في محافظة الزرقاء.
The study aimed at identifying the degree of the principals' practice of decision making and its relation to job performance from the point of view of educational counselors in secondary schools in Zarqa Governorate. The study sample consisted of (240) mentors and counselors from secondary school staff in the directorates of education in Zarqa Governorate. The study was applied in the first semester 2017/2018, and the study used the descriptive descriptive method. After analyzing the data, the study reached the results: The level of decision-making among high school principals in Zarqa was high. There are no statistically significant differences in the level of decision making and the dimensions of it in the secondary school principals in Zarqa due to gender variables, scientific qualification, years of experience, and type of school. The level of job performance of educational counselors in secondary schools in Zarqa Governorate is high. There are differences of statistical significance in the level of job performance of educational counselors in Zarqa Governorate according to gender variable, and in favor of guides. For the benefit of private school counselors, and for the benefit of educational counselors holders of a bachelor's degree. The existence of a positive correlative relationship and a statistically significant function between the decision-making level of secondary school principals and the level of job performance of educational counselors in secondary schools in Zarqa Governorate.
Keywords: اتخاذ القرارات -- الأداء الوظيفى -- المرشدين التربويين -- مديرى المدارس -- محافظة الزرقاء